An association study between nutritional status and eating habits of students from a Federal Technical School in the North of Minas Gerais, Brazil - Sá, Daniela Souza Santos de; Freitas, Ronilson Ferreira; Barroso, Roberta; Pereira, Eryka Jôvania; Freitas, Tahiana Ferreira; Caires, Nely Cristina Medeiros; Pereira, Juliana Andrade; Teixeira, Romero Alves (Research, Society and Development, 2024)
The present study aims to investigate the association between the nutritional status and eating habits of students from a federal technical school in the Northern region of Minas Gerais, Brazil. This is a cross-sectional study, with a random sample of 466 adolescents of both sexes, aged between 13 and 19 years of high school in a federal technical school in the North of Minas Gerais.Food consumption was assessed through a Habitual Intake Recall (RHAB). Weight and height were measured to assess nutritional status based on Body Mass Index (BMI) by age. The association between nutritional status and eating habits was verified by univariate analysis followed by multivariate linear regression.There was a prevalence of overweight of 15% among students. The variables that, after data analysis, remained in the multivariate logistic model, were associated with excess weight were: male gender, practice of physical activity.The prevalence of overweight among adolescents was below regional and national values, however overweight adolescents showed a significant difference in food intake regarding the intake of milk and dairy products compared to eutrophic adolescents.